Dalbavancin versus standard of care for the treatment of osteomyelitis in adults: A retrospective matched cohort study - Thamer A. Almangour; Gregory K. Perry; Abdullah A. Alhifany (Elsevier, 2020)
Objective: To assess the safety and effectiveness of dalbavancin compared to standard of care (SOC) in the treatment of osteomyelitis in adults. Method: A retrospective cohort study of patients with osteomyelitis due to S. aureus treated with dalbavancin was conducted. Patients who received at least 2 doses of dalbavancin for the treatment of osteomyelitis between January 1, 2015 to January 31, 2018 in a single center in Texas, USA were identified and matched in 1:1 ratio with controls who received SOC. The primary efficacy outcome was the clinical success at the end of treatment. Secondary efficacy outcome was the clinical success continued for at least 3 months after the completion of the antimicrobial therapy. Results: During study period, 21 patients received dalbavancin for the treatment of osteomyelitis; however, only 11 patients were eligible for inclusion and matched to 11 others who received SOC. Primary outcome was achieved in all 11 patients who received dalbavancin and all those patients subsequently attained the secondary outcome. In SOC group, primary outcome occurred in 82% (9/11) of patients in which 8 out of 9 patients subsequently achieved the secondary outcome. No adverse reaction noted in either group. Conclusion: Dalbavancin appears to be safe and effective for the management of osteomyelitis in adults. Further studies are needed to confirm these findings. Keywords: Dalbavancin, Osteomyelitis, Staphylococcus aureus, Retrospective Cohort